Rare bird documentation form for Red-necked Phalarope at Willow Slough, 1980 - Wilson, Barbara L.et al (1980)
Rare bird documentation form for seven Red-necked Phalaropes at Willow Slough in Mills County, IA on May 24, 1980. Epson - sheet feed/flatbed